GADGET TERHADAP PERKEMBANGAN ANAK PRA SEKOLAH: Gadget Terhadap Perkembangan Anak Pra Sekolah - Haerani, Mia; Qurrotua’ini, Hasna Aqiila; Ramdhan, Muhamad; Haryanto, Ricko Dwi (Jurnal Kesehatan Masa Depan, 2024)
Introduction: Etymologically, gadget is a term in English which means a small electronic device that has a special function. In Indonesian, gadgets are referred to as "acang". One of the things that distinguishes gadgets from other electronic devices is the element of "novelty". Purpose: of this study was to determine the impact of gadgets on the development of pre-school age children. Methods: used in this study is a literature study with a narrative method from research results published in 2017-2021. Literature search using a strategy with the keywords gadget and pre-school age development with the Google Scholar data base with the criteria used, namely the title of the article that discusses the relationship of gadgets to the development of pre-school children, availability of full text, samples, year of publication in the last 5 years. Results: From 10 articles, it was found that the influence of gadgets on the development of pre-school children was positive or negative. Conclusion: this study found an imbalance between positive and negative impacts where more negative impacts were obtained from using gadgets because pre-school age children could not use gadgets according to their needs. Therefore, the role of parents is needed in this case because it is to limit their children from using gadgets with the recommended time of 1-2 hours per day.